Ḥaidarābād nagīnah : Roznāmah Siyāsat, Ḥaidarābād meṉ ma̤tbūʻah mushtarakah nigārishāt kā intiḵẖāb (Silsilah-yi ma̤tbūʻāt-i Roznāmah Siyāsat, 1979)
Humorous articles using expressions and phrases peculiar to Dakhini Urdu; previously published in Siyāsat, Urdu daily.